Comparative analyses of morphological characters in Sphaerodoridae and allies (Annelida) revealed by an integrative microscopical approach - Helm, Conrad; Capa, María (Frontiers in Marine Science, 2015)
Sphaerodoridae is a group of benthic marine worms (Annelida) characterized by the presence of spherical tubercles covering their whole surface. They are commonly considered as belonging to Phyllodocida although sistergroup relationships are still far from being understood. Primary homology assessment of their morphological features are lacking, hindering the appraisal of evolutionary relationships between taxa. Therefore, our detailed morphological investigation focuses on different Sphaerodoridae as well as on other members of Phyllodocida using an integrative approach combining scanning electron microscopy (SEM) as well as immunohistochemistry with standard neuronal (anti-5-HT) and muscular (phalloidin-rhodamine) markers and subsequent CLSM analysis of whole mounts and sections. Furthermore, we provide histological (HES) and light microscopical data to shed light on the structures and hypothetical function of sphaerodorid key morphological features. We provide fundamental details into the sphaerodorid morphology supporting a Phyllodocida ancestry of these enigmatic worms. However, the muscular arrangement and the presence of an axial muscular pharynx is similar to conditions observed in other members of the Errantia too. Furthermore, nervous system and muscle staining as well as SEM and histological observations of different types of tubercles indicate a homology of the so called microtubercles, present in the long-bodied sphaerodorids, to the dorsal cirri of other Errantia. The macrotubercles seem to represent a sphaerodorid autapomorphy based on our investigations. Therefore, our results allow comparisons concerning morphological patterns between Sphaerodoridae and other Phyllodocida and constitute a starting point for further comparative investigations to reveal the evolution of the remarkable Sphaerodoridae.